Sticky cost determinants: Which one has the stronger impact? - Michelle Soegiharto; Dyna Rachmawati (The Indonesian Accounting Review, 2022)
Sticky cost is a phenomenon that can occur in companies and it is an unbalanced response of costs to changes in output. Since it can reduse company profits, it should not occur. Therefore, it is important to know the determinants that influence it so that the company can control properly redusing it. The aim of this research is to test which the determinants that have the impact of Covid-19, asset intensity, employee intensity, equity intensity, management incentives, profitability, and intellectual capital on sticky cost.This research is a quantitative research with  object of manufacturing companies listed on the Indonesia Stock Exchange with observation period of 2019-2020. This research uses financial data from annual report and summary of minutes General Meeting of Shareholders. The sample selection technique used purposive sampling method. This research involved two data analysis techniques. There are multiple linear regression for main test and logistic regression for additional test. The results of the main test show that employee intensity and intellectual capital have impact on sticky cost. But, the Covid-19, asset intensity, equity intensity, management incentives, and profitability have no impact on sticky cost. The main test result is supported by the additional test, in term of first, intellectual capital has impact on sticky cost. Second, the other determinants remain no impact on sticky cost. The implications of this research are management should be carefull to make investment in intangible assets and use employee intensive. As those determinants can increase sticky cost.